Christology : origins, developments, debates - O'Collins, Gerald (Waco, Texas : Baylor University Press, 2015)
Gerald O'Collins continues his groundbreaking work in Christology by first tracing its major developments over the last fifty years.He next turns to a theology of resurrection--Christology's central event--and the foundational roles played by its two great witnesses,Peter and Paul. O'Collins then masterfully constructs a "theology of religions" that explores the relationship of Christianity to other living faiths precisely in light of the priesthood of Jesus Christ.
Christology : the last fifty years -- Revisiting the person of Jesus -- Revisiting the work of Jesus -- Paul as a witness to the risen Jesus -- Peter as witness to easter -- The priesthood of Christ and followers of other faiths -- Jacques Dupuis and religious pluralism -- Jacques Dupuis and Karl Rahner.
Includes bibliographical references and index.
Keywords: Jesus Christ -- Person and offices; Jesus Christ -- History of doctrines